A INFLUÊNCIA DA DOR NO TEMPO DE INTERNAÇÃO E DESFECHOS CLÍNICOS NO MUNICÍPIO DE ANÁPOLIS-GOIÁS NO ANO DE 2022 (CIPEEX, 2026)
Introduction: Chronic pain (CP) is a global public health problem with a high prevalence in Brazil, impacting the quality of life. Classified as either primary or secondary, it varies by age and gender (more common in women and the elderly). Brazilian studies on this topic are scarce. Objectives: This study sought to understand the relationship between chronic diseases, acute diseases, age, sex, hospital stay, and deaths in Anápolis-GO in 2022. We investigated the impact of secondary pain on hospitalization, the association between age and death, and trends in length of stay by age and sex. Method: This was a quantitative, descriptive, and deductive study that used secondary data from Hospitalization Authorizations (AIHs) from DataSUS for the year 2022 in Anápolis-GO. Age groups, sex, costs, and days of hospitalization were analyzed. Data was processed using Excel and statistical analysis was performed with SPSS/R (regression, ANOVA). Results: Primary pain diagnoses resulted in zero or minimal hospitalization. However, chronic diseases (e.g., heart failure: 1,687 days; mental disorders: 1,623 days) accounted for the longest stays. There were no direct deaths from primary pain; most deaths occurred in patients over 50 years old with severe chronic diseases. Men had longer hospital stays for certain pulmonary diseases. Conclusions: Primary pain did not lead to prolonged hospitalizations or deaths. There is a strong correlation between advanced age, chronic diseases, longer hospital stays, and mortality. Pain is a relevant secondary symptom. Effective management is crucial for improving quality of life and optimizing hospital management.
Keywords: Dor; Hospitalização; Causas de morte